2004
DOI: 10.1258/135763304323070779
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for multidisciplinary lung cancer meetings

Abstract: According to recent UK guidelines on the management of lung cancer, all cases should be reviewed prospectively by a lung cancer multidisciplinary team (MDT) and a thoracic surgeon should be readily available to liaise with the MDT. However, there is a shortage of thoracic surgeons in the UK. Over a one-year period, 28 MDT meetings were held at a district general hospital in Southend, at which 62 patients were presented to a tertiary cardiothoracic centre in London, 80 km away, via ISDN videoconferencing at 384… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 5 publications
0
63
0
Order By: Relevance
“…There were 16 studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that met the criteria for inclusion and these were published between 1994 and July 2007. MD team working is a relatively new concept in the management of lung cancer patients, so it was not surprising that there were no published studies before 1994.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 16 studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that met the criteria for inclusion and these were published between 1994 and July 2007. MD team working is a relatively new concept in the management of lung cancer patients, so it was not surprising that there were no published studies before 1994.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Seven of the studies were before-and-after designs [9][10][11][12][13][14][15]. Four included only NSCLC patients [9,12,14,15] and one of these [9] only included patients older than 70 years and another only inoperable NSCLC cases [14].…”
Section: Before-after Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials reported outcomes before and after the implementation of MDTs; only three of these included a small number of patients with SCLC [10][11][12]. A systematic review by COORY et al [3] identified only one randomised trial [13] including SCLC investigating the impact of MDTs.…”
Section: Role Of Multidisciplinary Teamsmentioning
confidence: 99%
“…Spatial issues should not be a limiting factor nowadays; depending on the setting, a telecommunication solution might be implemented when physical meetings are difficult [12].…”
Section: Role Of Multidisciplinary Teamsmentioning
confidence: 99%